UPAYA UNIAP DALAM MENANGANI HUMAN TRAFFICKING DI THAILAND - Desy Lucia Ariyanti Arby; Christy Damayanti; GPH Dipokusumo (Solidaritas, 2020)
This thesis entitled UNIAP attempt of dealing with Human Trafficking in Thailand. Human Trafficking rate in Thailand are increases over year. The victims are employed with low wage and even made a sexual worker. Thailand government has taken some attempt to deal with the human trafficking and humanity problem, one of which is to cooperate with The International Organization together with UNIAP, involve neighboring country such a Myanmar, Laos, Cambodia, Vietnam. The research method employed was Descriptive Qualitative Research; technique of collecting to this study. The theories used were International and Human Security theories. The result of the research used to against Human Trafficking in Thailand, UNIAP was also make an agreement with the MOU together with neighboring country. Prevention, do a campaign to raise awareness about Human Trafficking. Protection, do a rescue, identification, rehabilitation and legal assistance. Prosecution, enforce rules regarding Anti Trafficking in Persons Act B.E 2551 (2008). Keywords : Human Trafficking, Thailand, UNIAP.